Enhancing procurement of security services: a comparative case study of Mangaung and Kimberly Correctional Centres - Cenge, Ntandokazi Nikiwe (Research of GSB, 2018)
This aim of this research is to explore two methods for procuring security services in South Africa. This research is a comparative case study between two correctional centers, which are the Mangaung Correctional Centre and the Kimberly Correctional Centre. The Mangaung Correctional Centre has been procured through Public-Private Partnership, where government procures services through a private party and the Kimberly Correctional Centre has been procured through the traditional public sector finance method. The main objectives of the study is to compare and contrast the costs of incarceration in these correctional centres; to evaluate the quality of security services provided in these two correctional centres as well as to examine the most economic, efficient and effective method of procuring security services. The research findings indicated that the incarceration costs for Mangaung Correctional Centre were far more than the costs for Kimberly Correctional Centre, which poses a threat of affordability for the Department of Correctional Services. The research study also found in terms of the quality of security services provided in Mangaung Correctional Centre, there have been no escapes or riots reported in the centre for a very long time, on the other hand, the research has found that there has been a compromise in the quality of security services provided in Kimberly Correctional Centre because the centre has experienced violent riots in the recent years and there has been security threats due to the loss of the master key. It emerged from the research findings that there is generally a lack of monitoring and evaluation especially when it comes to the issue of incarceration costs in Mangaung Correctional Centre because the costs have increased by more than 100 per cent since inception, this is far more than increase in average inflation for the period reviewed. The research concluded by providing recommendations for consideration of procuring security services in future. Some of the key recommendations made in this research are that before government enters into any major contract, unless the feasibility study confirms the affordability of the project, then the government should not pursue the project further. The research further recommended that the government negotiators represented in the negotiation processes and awarding contracts should be capacitated, more especially in the area of finance and law to ensure that they understand the complexities and technicalities involved during the processes.